A closer insight into the mechanism operating in the trifluoroacetylation of pyrrole. New trifluoromethyl pyrroylmethane discovered - Peláez, Walter José (2009)
A former studied reaction of acetylation of pyrrole was revisited and this allowed the identification of new compounds and the isolation and characterization of a very stable solid (2,2′,2″-(2,2,2-trifluoroethane-1,1,1-triyl)tris(1H-pyrrole)). All these materials were probably missed, buried in the black tar that characterizes the reaction. A careful and thorough selection of the reaction's conditions provided both evidence for three new compounds and a closer insight into the mechanism operating at room and lower temperatures.